ReMMoS - Um Modelo de Replicação em Ambientes que Suportam Mobilidade de Objetos - Ferrari, Débora Nice; Vargas, Patrícia Kayser; Geyer, Cláudio Fernando Resin (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2000: Anais do I Workshop em Sistemas Computacionais de Alto Desempenho, 2000)
Mobility and replication are frequently used in distributed systems composed by heterogeneous network, distant and connected by different hosts of communications. However there are few systems that deal with both techniques mainly in distributed object environments. This paper presents the ReMMoS - Replication Model in Mobility Systems. The replication in distributed systems can be used to offer security and reliability and also to increase execution performance in applications. This paper presents a replication model in distributed object systems with mobility aiming to get better performance. The mobility is explicit and the replication is implicit. So, programmers do not need to worry about management and consistency of the replicated copies. The model's implementation is in progress and is briefly presented.